Analysis of the assortment of medicines and dietary supplements that can reduce the risk of carbohydrate metabolism disorders - Dub , Anastasiia; Kryshtal, Oleksandra; Pokotylo , Olena (The Ukrainian Scientific Medical Youth Journal, 2025)
more than 537 million adults were diagnosed with diabetes mellitus in 2021, and according to projections by the International Diabetes Federation, this number may rise to 783 million by 2045. Prevention and correction of carbohydrate metabolism disorders are gaining increased relevance within the framework of current approaches to the management and prevention of metabolic diseases, particularly through dietary modifications and the use of dietary supplements. The aim of the study was to systematize data on medicinal products and dietary supplements intended to reduce the risk of developing carbohydrate metabolism disorders, as represented on the contemporary pharmaceutical market of Ukraine. The research was based on data obtained from the State Register of Medicinal Products of Ukraine, the electronic reference system "Compendium," and the online resource tabletki.ua. As a result of the conducted study, it was determined that the total assortment of products potentially used for the prevention of carbohydrate metabolism disorders comprises 198 items, of which the majority are dietary supplements (82.32%), while medicinal products account for only 17.68%. This disproportionality may be attributed to the lower level of regulatory oversight regarding dietary supplements, their wide availability, simplified registration procedures, active marketing strategies, and high consumer demand. A significant proportion of both medicinal products and dietary supplements are of domestic origin (62.9% and 79.75%, respectively), reflecting the competitiveness of Ukrainian manufacturers. In the medicinal product segment, the leading manufacturer is PJSC "Liktravy," while in the dietary supplement segment, it is LLC "Klyuchi Zdorovia." Regarding dosage forms, medicinal products are predominantly represented by herbal raw materials, tablets, and infusion solutions, whereas dietary supplements are most frequently available as herbal raw materials, capsules, and tablets, meeting the needs of diverse consumer groups. An analysis of the ingredient composition revealed that medicinal products are primarily monocomponent (74.3%), consistent with the principles of evidence-based medicine, while dietary supplements often contain multicomponent formulations (47.2%) aimed at exerting complex effects on metabolic processes. An important prospective change in the market is expected following the adoption of the Law of Ukraine № 4122-IX in 2024, which strengthens state control over the quality, safety, and circulation of dietary supplements, thus harmonizing national legislation with European Union standards. Nonetheless, further research is warranted to evaluate the physical and economic accessibility of such products to consumers, and their compliance with quality standards.